Diet Quality and Its Effect on Weight Gain Prevention in Young Adults: A Narrative Review - Martin, Julie C.; Moran, Lisa J.; Harrison, Cheryce L. (Seminars in Reproductive Medicine, 2020)
Global environmental and societal changes have resulted in an increased consumption of energy-dense foods contributing to escalating obesity prevalence, with most rapid weight gain occurring in young adults. Diet is one major modifiable factor contributing to escalating obesity prevalence. Understanding overall diet quality of populations at high risk for weight gain and obesity development, including young adults, provides evidence of dietary intakes, dietary patterns, and associated behaviors, to inform the development of targeted interventions aimed at the prevention of weight gain. This narrative review synthesizes the current evidence of the association between diet quality and weight gain in young adults. Overall, there is a consistent direction of association between improved diet quality and reduced weight gain in adults. This demonstrates the potential of small improvements in diet quality over time as a probable contributor to minimizing weight gain in young adults. Future research evaluating environmental nutrition policies with associated change in diet quality and prospective weight change in population-based studies is warranted to determine their longer-term impact in improving overall diet quality as one strategy to halt escalating obesity prevalence rates.
Keywords: diet quality; obesity; young adult; weight gain; prevention